Monocytes treated with human immunodeficiency virus Tat kill uninfected CD4(+) cells by a tumor necrosis factor-related apoptosis-induced ligand-mediated mechanism - Yang, Yida; Tikhonov, Ilia; Ruckwardt, Tracy J; Djavani, Mahmoud; Zapata, Juan Carlos; Pauza, C David; Salvato, Maria S (Journal of virology, 2003)
The human immunodeficiency virus (HIV) Tat protein has a critical role in viral transcription, but this study focuses on its additional role as an extracellular effector of lymphocyte cell death. It is well known that Tat induces tumor necrosis factor-related apoptosis-induced ligand (TRAIL) in peripheral blood mononuclear cells (PBMC), and we show that the majority of TRAIL is produced by the monocyte subset of PBMC. Human monocytes and U937 monoblastoid cells did not take up soluble HIV Tat-86, as T cells did, yet produced more TRAIL than did T cells. TRAIL secretion was induced by Tat and by a cysteine-rich peptide of Tat but not by sulfhydryl-modified Tat toxoid. Although there was only a slight increase in cell surface expression of TRAIL on monocytes, sufficient TRAIL was secreted to be toxic for T cells. The cytotoxicity of Tat-stimulated monocyte medium could be blocked by a TRAIL-neutralizing antibody. T cells treated with Tat did not secrete enough TRAIL to mediate cell death in our assay. Remarkably, uninfected T cells are more susceptible to TRAIL than are HIV-infected T cells. The production of TRAIL by Tat-stimulated monocytes provides a mechanism by which HIV infection can destroy uninfected bystander cells.